2000
DOI: 10.1007/s005920070020
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping behavior in patients with diabetes mellitus

Abstract: Diabetes mellitus is a disease which must be controlled over the lifetime of a patient. We investigated the issues of stress and coping for diabetes mellitus which may influence self-management. In addition, we examined the association of these factors with blood glucose control, in order to review self-management instructions for diabetes mellitus. The study included 153 patients with diabetes mellitus. The patients were divided into two subgroups: good-control group, comprising patients with glycohemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…HbA 1c % was higher when people with DM1 reported frequently eating at regular times. People with poorly controlled diabetes may follow their diabetes treatment more rigidly compared to people with good control [38]. We cannot explain the differences between DM1 and DM2.…”
Section: Discussionmentioning
confidence: 90%
“…HbA 1c % was higher when people with DM1 reported frequently eating at regular times. People with poorly controlled diabetes may follow their diabetes treatment more rigidly compared to people with good control [38]. We cannot explain the differences between DM1 and DM2.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, there is a two-way relationship between chronic stress and poor adherence. For example, Nomura et al (2000) reported that among people with T1DM and T2DM, stress leads to poor adherence and thus poor glucose control. They also noted that non-adherence to self-management behaviours may have caused stress.…”
Section: Life Stressmentioning
confidence: 98%
“…Using a direct approach, studies have shown that children with high life stress tend to have worse glycemic control . Other research, using an indirect approach, found an adverse effect of diabetes stress on diabetes self‐management . There is support from intervention studies targeting diabetes stress for improved glycemic control .…”
Section: Stress and Copingmentioning
confidence: 99%